2003
DOI: 10.1128/jcm.41.11.5011-5014.2003
|View full text |Cite
|
Sign up to set email alerts
|

Metronidazole-Resistant Helicobacter pylori Is More Prevalent in Patients with Nonulcer Dyspepsia than in Peptic Ulcer Patients in a Multiethnic Asian Population

Abstract: The trend of increasing prevalence of antibiotic resistance among Helicobacter pylori strains has been suggested as a cause of the failure of treatment of H. pylori infections. In this study, 120 of 211 antral biopsy specimens from patients with dyspeptic symptoms were found to harbor H. pylori. The isolates from the 120 specimens were tested by the agar dilution method, and 38 (31.7%) were found to be metronidazole resistant. Among the 211 subjects, 81 of 115 (70.4%) patients with peptic ulcer (PU) were infec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
1

Year Published

2004
2004
2014
2014

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 25 publications
1
4
1
Order By: Relevance
“…A similar, if less, pronounced effect was seen in a recent Italian study of CLA resistance [19]. It differs from data from an Asian cohort, where patients with PUD were more likely to harbour MTZ-resistant strains than patients with NUD [39]. The rate of PUD varied less based on antibiotic sensitivity in our study.…”
Section: Discussioncontrasting
confidence: 66%
“…A similar, if less, pronounced effect was seen in a recent Italian study of CLA resistance [19]. It differs from data from an Asian cohort, where patients with PUD were more likely to harbour MTZ-resistant strains than patients with NUD [39]. The rate of PUD varied less based on antibiotic sensitivity in our study.…”
Section: Discussioncontrasting
confidence: 66%
“…Metronidazole resistance was more common in patients born in towns (27.6 %, 56 of 203) than in those born in villages (12.7 %, 8 of 63, P50.016). Another study has also detected non-ulcer patients to be associated with a higher metronidazole resistance rate (Lui et al, 2003). An inverse association has been reported in Spain (Ferrero et al, 2000).…”
Section: Resultsmentioning
confidence: 86%
“…This sustained high level of metronidazole resistance prior to H. pylori eradication therapy could be attributed to massive prescription of metronidazole as a common anti-parasite drug and for other gynaecologic diseases in many developing countries [37]. Moreover, these high prevalence of metronidazole resistance rate has also been well-documented in neighbouring Southeast Asian countries such as Vietnam (69.9%) [38], Thailand (30.4%) [39], and Singapore (31.7%) [40]. Therefore, in agreement with other previous studies [21], [26], we have further confirmed that metronidazole should not be the choice for first line H. pylori eradication therapy in the local population [20].…”
Section: Discussionmentioning
confidence: 99%